DOCKING OF 1-PHENYLSULFONAMIDE-3-TRIFLUOROMETHYL-5-PARABROMOPHENYL-PYRAZOLE TO CYCLOOXYGENASE-2 USING PLANTS - Stefanus Layli Prasojo; Fajar Agung Dwi Hartanto; Nunung Yuniarti; Zullies Ikawati; Enade Perdana Istyastono (Universitas Gadjah Mada, 2010)
The docking protocols to virtually screen selective cyclooxygenase-2 (COX-2) ligands using PLANTS docking software were developed and validated. The crystal structure of 1-phenylsulfonamide-3-trifluoromethyl-5-parabromophenyl-pyrazole (S58) binds to cyclooxygenase-2 (COX-2) was used as the reference structure. The developed protocols could predict the binding pose of S58 to COX-2 accurately (RMSD is 1.2 Ǻ).